Factors associated with delays in medical and surgical open facial fracture management - David Hamilton; David Bar-Or; Kaysie L Banton; Therese M Duane; Erica Sercy; Jeffrey Gordon; Brian Blackwood; Andrew Hentzen; Matthew Hatch (Trauma Surgery & Acute Care Open)
Objectives Open fractures are at risk of infection because of exposure of bone and tissue to the environment. Facial fractures are often accompanied by other severe injuries, and therefore fracture management may be delayed until after stabilization. Previous studies in this area have examined timing of multiple facets of care but have tended to report on each in isolation (eg, antibiotic initiation).Methods This was a retrospective study of adult patients admitted to five trauma centers from January 1, 2017 to March 31, 2021 with open facial fractures. Variables collected included demographics, injury mechanism, details on facial and non-facial injuries, facial fracture management (irrigation and debridement (I&D), irrigation without debridement, open reduction internal fixation (ORIF), antibiotics), and other hospital events. The study hypothesized that the presence of serious non-facial injuries would be associated with delays in facial fracture management. The primary aims were to describe open facial fracture management practices and examine factors associated with early versus delayed fracture management. A secondary aim was to describe infection rates. Early treatment was defined as within 24 hours of arrival for I&D, irrigation without debridement, and ORIF and within 1 hour for antibiotics.Results A total of 256 patients were included. Twenty-seven percent had major trauma (Injury Severity Score ≥16). The presence of serious head injury/traumatic brain injury was associated with delayed I&D (ORearly=0.04, p<0.01), irrigation without debridement (ORearly=0.09, p<0.01), and ORIF (ORearly=0.10, p<0.01). Going to the OR within 24 hours was associated with early I&D (ORearly=377.26, p<0.01), irrigation without debridement (ORearly=13.54, p<0.01), and ORIF (ORearly=154.92, p<0.01). The infection rate was 4%.Conclusions In this examination of multiple aspects of open facial fracture management, serious injuries to non-facial regions led to delays in surgical fracture management, consistent with the study hypothesis.Level of evidence Level III, prognostic/epidemiological.